DIGITAL BRANDING UNTUK MEMBANGUN CITRA LEMBAGA DI BALAI LATIHAN KERJA (BLK) SURABAYA - Afifah, Fitri’Atul (STKIP Pesisir Selatan, 2025)
Objective: One strategy that can be implemented to strengthen the existence and build a positive image of the institution is through